Optimal Portfolio Comparison Based on Markowitz and Single Index Model Using IDX BUMN20 Stocks during Covid-19 - Husni, Ricky Albert; Samosir, Tumpal; Sindhuarta, Siji Jati (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
The study aims to compare between an optimal portfolio of stocks formed with the Markowitz model and those formed with the Single Index model during the Covid-19 pandemic. This study's goal is to determine which model will give a higher expected return or lower portfolio risk. Samples used are the stocks member of index IDX BUMN20 which never leave the index, never had changes in shares amount in major and minor reviews, also didn’t do stock split along the period of January 2020 – January 2022. The study method used is a quantitative method with a cross-sectional approach. The results show that both higher expected returns and lower portfolio risk are given by the Single Index model. This demonstrates that the optimal portfolio formed with the Single Index model is better than those formed with the Markowitz model.